Multi-Task Learning Architectures for Joint Interference Detection and KPI Prediction in 5G Networks - Kaviani, Mina; Almeida, Jurandy; Verdi, Fábio L.; Souza, Ricardo (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Real-time interference detection and accurate Key Performance Indicator (KPI) prediction are critical for optimizing 5G radio access networks. Jointly addressing these objectives offers a comprehensive view of network behavior but presents a significant challenge: simultaneously optimizing for heterogeneous tasks—discrete interference classification and continuous KPI regression—often leads to negative transfer or inefficient parameterization. In this paper, we systematically investigate the effectiveness of Multi-Task Learning (MTL) for this dual objective by evaluating distinct architectural strategies, including Hard Parameter Sharing, Cross-Stitch networks, Multi-gate Mixture-of-Experts (MMoE), Progressive Layered Extraction (PLE), and an attention-based model, against a Single-Task Learning (STL) baseline. Using a dataset collected from a realistic 5G testbed, we analyze the trade-offs between classification accuracy, regression error, model complexity, and inference latency. Our experimental results demonstrate that no single architecture dominates across all metrics. While STL achieves high predictive performance, it is computationally prohibitive for real-time applications due to redundant feature extraction. Conversely, Hard Parameter Sharing offers minimal latency but suffers severe performance degradation due to rigid representation sharing. PLE delivers the highest classification accuracy (87.62%) but at the cost of increased model size. Ultimately, MMoE emerges as the optimal architecture for practical deployment; it achieves the lowest total test loss and high classification accuracy (86.80%) while reducing Floating Point Operations (FLOPs) by approximately 74% compared to STL, making it well-suited for practical interference-aware monitoring and optimization in 5G radio access networks.